1821: The celebration of the Independence of Peru in Santiago de Chile - Sánchez Rodríguez, Susy (2021)
This article focuses on the celebration of the Peruvian Independence in the city of Santiago de Chile in August 1821. It mainly examines the official newspaper, Gazeta Ministerial de Chile. This work establishes the intense festivities that produced the so-called liberation of Lima, which occurred on July 10, 1821. On this date, the patriotic forces under the command of General San Martín entered the city. The first part shows the highly symbolic link between the identified liberation of Lima from the royalist forces with the “disaster of Rancagua.” The “liberation of Lima” led to a resignification of the commemoration of the battle of Rancagua. The second part demonstrates how the set celebration of the Peruvian Independence sublimized the political and symbolic legitimacy of the Supreme Director, Bernardo O’Higgins, who became a heroic continental military figure, turning him into the embodiment of a triumphant nation.